Application of quality control circle activities in improving accuracy of rational diet for hospitalized patients with diabetes mellitus (运用品管圈提高住院糖尿病患者合理膳食精准率) - SONG Chunmiao (宋春苗); SONG Shuxian (宋书贤); DING Yi (丁奕); KANG Geping (康格平); WANG Yuena (王岳娜); XU Yuanle (许远乐); ZHOU Miao (周苗) (中西医结合护理)
Objective To improve the accuracy of rational diet and the quality of life in hospitalized patients with diabetes mellitus by using quality control circle activities. Methods The problem-solving QCC activities were carried out, and the corresponding countermeasures were formulated and implemented, including the establishment of a systematic health education model, the establishment of a multi-dimensional training system, and establishment of a perfect catering mechanism in the canteen. Results The accurate rate of rational diet in hospitalized diabetic patients increased from 45. 52% before implementation of QCC activities to 77. 99% after implementation of QCC activities. Conclusion The QCC activities can improve the accurate rate of rational diet for hospitalized patients with diabetes mellitus, effectively improve the blood sugar level, improve the self-management ability, delay disease progression, and improve the quality of life. (目的 探讨品管圈活动提高住院糖尿病患者合理膳食精准率的效果, 旨在改善患者生活质量。方法 开展问题解决型品管圈活动, 通过现状分析、原因解析, 制定针对性对策并实施, 包括构建系统化健康教育模式、建立多维度培训体系、建立完善的食堂配餐机制等。结果 住院糖尿病患者合理膳食精准率从品管圈活动实施前的45. 52%提升至品管圈活动实施后的77. 99%。结论 通过品管圈活动, 能提高住院糖尿病患者合理膳食精准率, 有助于改善住院糖尿病患者的血糖水平, 提高患者自我管理能力, 延缓疾病进展, 提高生活质量。)